Long-term outcomes in patients with acute pulmonary embolism after in-hospital treatment: study protocol of the prospective Lungenembolie Augsburg Studie (LEA study) - Jakob Linseisen; Inge Kirchberger; Wolfgang von Scheidt; Thomas M Berghaus (BMJ Open)
Introduction Acute pulmonary embolism (PE) is a frequent life-threatening event and an important cause of hospitalisation, morbidity and mortality worldwide. Limited information on the long-term course of PE patients is available so far. The Lungenembolie Augsburg study will provide a view on the predisposing and PE-provoking factors, diagnostic procedures and short as well as long-term treatment options. Especially, the data on the long-term course of the disease—in combination with omics data obtained in biospecimens—will generate new knowledge regarding triggers, disease progression, treatment, long-term sequelae, prognosis and prevention of disease recurrence.Methods and analysis In this prospective study, we will include about 1000 patients admitted to the university hospital of Augsburg, aged 18 years and older with a confirmed diagnosis of acute PE. At baseline, demographic information, symptoms on presentation, delay in diagnosis, predisposing and PE-provoking factors, comorbidity, quality of life, symptoms of anxiety and depression, information on invasive and non-invasive treatment procedures, complications and laboratory parameters will be collected. During the hospital stay, 30 mL blood will be collected from the patients, processed, aliquoted and frozen at −80°C. In a subgroup of patients, an eight-channel polygraphy will be carried out to assess sleep-disordered breathing. All study participants will be followed up for 60 months via postal questionnaires or telephone interviews after hospital discharge. Long-term survival, bleeding complications and PE recurrence during the follow-up are the primary study outcomes. To identify risk factors and determinants associated with these outcomes, confounder-adjusted Cox-regressions will be used for modelling and to estimate relative risks. Effect modification by age and sex will be examined.Ethics and dissemination The study protocol was approved by the Ethics Committee of the Ludwig-Maximilians-Universität München (Date of approval: 1 August 2017, Reference number: 17-378). Study results will be presented at national and international conferences and published in peer-reviewed scientific journals.